2004
DOI: 10.1038/sj.sc.3101559
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment of the injured human spinal cord by means of functional magnetic resonance imaging

Abstract: Study design: A magnetic resonance imaging technique that enables indirect detection of neuronal activity has been developed for the spinal cord. In the present study, this method, spinal functional magnetic resonance imaging (fMRI), is applied to the first study of the injured spinal cord, with the goal of better clinical assessment of the entire cord. Objectives: The objectives of this project are: (1) to investigate the neuronal activity that can be detected in the spinal cord caudal to a chronic injury by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
102
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 32 publications
0
102
2
1
Order By: Relevance
“…The activity detected is in agreement with known physiology and together with previous findings of increased contralateral activation in response to stimulation of the injured spinal cord suggest that spinal fMRI is providing reliable results. 2,[16][17][18][19] This occurrence and the implications for recovery of function in injured persons have recently come under closer investigation. 19 Investigation of neuronal circuitry caudal to a spinal cord injury site is required.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The activity detected is in agreement with known physiology and together with previous findings of increased contralateral activation in response to stimulation of the injured spinal cord suggest that spinal fMRI is providing reliable results. 2,[16][17][18][19] This occurrence and the implications for recovery of function in injured persons have recently come under closer investigation. 19 Investigation of neuronal circuitry caudal to a spinal cord injury site is required.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Spinal fMRI reveals neuronal function indirectly via changes in blood flow and blood oxygen levels that occur near metabolically active gray matter. 4 The signal change arises in part from the blood oxygen leveldependant (BOLD) contrast, which is based on the metabolic activity that occurs in active neuronal tissues.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, seminal studies have shown that spinal cord fMRI is feasible and enables to obtain reliable results both in healthy subjects [Govers et al, 2007;Komisaruk et al, 2002;Kornelsen and Stroman, 2004;Li et al, 2005;Madi et al, 2001;Maieron et al, 2007;Moffitt et al, 2005;Ng et al, 2006;Stracke et al, 2005;Stroman and Ryner, 2001;Stroman et al, , 2002aStroman et al, , 2003aStroman et al, , 2005aYoshizawa et al, 1996] and in patients with spinal cord injury [Kornelsen and Stroman, 2007;Stroman et al, 2002bStroman et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%